N3‐Kethoxal‐Based Bioorthogonal Intracellular RNA Labeling. (5th February 2021) - Huang, Jinguo; Zhao, Ruiqi; Mo, Jing; Wang, Fang; Weng, Xiaocheng; Zhou, Xiang
Abstract: There is growing interest in developing intracellular RNA tools. Herein, we describe a strategy for N3 ‐kethoxal (N3 K)‐based bioorthogonal intracellular RNA functionalization. With N3 K labeling followed by an in vivo click reaction with DBCO derivatives, RNA can be modified with fluorescent or phenol groups. This strategy provides a new way of labeling RNA inside cells. Abstract : The small, membrane‐permeable probe N3 ‐kethoxal has low toxicity and highly selectivity for reaction with guanine allowing it to introduce azido groups into RNA within a cellular environment. This N3 K‐assisted bioorthogonal intracellular RNA strategy provides a great prospect for in vivo RNA labeling to develop various RNA tools for RNA functional research.